2021
DOI: 10.1002/adfm.202102035
|View full text |Cite
|
Sign up to set email alerts
|

“Water‐in‐Deep Eutectic Solvent” Electrolytes for High‐Performance Aqueous Zn‐Ion Batteries

Abstract: Aqueous Zn‐ion batteries have been considered as promising alternatives to Li‐ion batteries due to their abundant reserves, low price, and high safety. However, Zn anode shows poor reversibility and cycling stability in most conventional aqueous electrolytes. Here, a new type of aqueous Zn‐ion electrolyte based on ZnCl2–acetamide deep eutectic solvent with both environmental and economic friendliness has been prepared. The water molecule introduced in the “water‐in‐deep eutectic solvent” electrolyte could redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 41 publications
2
132
0
Order By: Relevance
“…These results are superior to recently reported Zn symmetrical cells with DEEs (Table S1, Supporting Information). [25][26][27]29] Scanning electron microscopy (SEM) was used to investigate the morphology of the Zn electrodes in the Zn|AE|Zn and Zn|Z6S|Zn cells after 50 cycles. The Zn electrode from the cycled Zn|AE|Zn cell was rough and porous, indicating severe corrosion due to the AE (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are superior to recently reported Zn symmetrical cells with DEEs (Table S1, Supporting Information). [25][26][27]29] Scanning electron microscopy (SEM) was used to investigate the morphology of the Zn electrodes in the Zn|AE|Zn and Zn|Z6S|Zn cells after 50 cycles. The Zn electrode from the cycled Zn|AE|Zn cell was rough and porous, indicating severe corrosion due to the AE (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lewis acids (e.g., Li + , Na + , and Zn 2+ ), can be mixed with Lewis bases (e.g., succinonitrile, acetamide, and urea) to produce DEEs. [ 22,24–27 ] In that context, Qiu et al. reported an acetamide/ZnTFSI‐based DEE, which effectively suppressed dendrite growth and side reactions on ZMA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep eutectic solvents (DES), as a kind of "green" solvent, have been studied to protect the Zn metal anode for AZIBs [17][18][19]. Meanwhile, it also exhibits a certain antifreezing property due to the interaction with water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Deep eutectic solvent, a eutectic mixture of Lewis/Brønsted acidic anion and alkaline cation, is a new type of ionic liquid that can maintain thermal stability at room temperature. 23,24 While used as electrolytes for zinc-based batteries, it was found that anodic zinc revealed a more stable plating/stripping process, but the disadvantage of poor Zn 2+ diffusion efficiency caused by low electron conductivity and high viscosity was also prominent. 25 The extra addition of small molecular cosolvents ( e.g.…”
Section: Introductionmentioning
confidence: 99%